2022
DOI: 10.1128/spectrum.02176-21
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of SARS-CoV-2 Variants B.1.1.7 (Alpha) and B.1.617.2 (Delta) Using a One-Step Quantitative PCR Assay

Abstract: The new assays described herein enable rapid, straightforward, and cost-effective detection of severe acute respiratory syndrome coronavirus 2 (SC-2) with immediate classification of the examined sample as Alpha, Delta, non-Alpha, or non-Delta variant. This is highly important for two main reasons: (i) it provides the scientific and medical community with a novel diagnostic tool to rapidly detect and classify any SC-2 sample of interest as Alpha, Delta, or none and can be applied to both clinical and environme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While sequencing provides complete information on the examined sample, it is expensive, not readily amendable for high throughput, and it is limited by the sample quality. We recently demonstrated that variant-specific PCR can determine SC-2 variant identity in cases of poor sample quality where sequencing fails [41]. Here, we show that variant-specific PCR can be a valuable tool to rapidly identify variant dynamics in WW in a cost-effective manner, which in turn enables a large-scale screening of WW samples to obtain important epidemiological information.…”
Section: Discussionmentioning
confidence: 83%
“…While sequencing provides complete information on the examined sample, it is expensive, not readily amendable for high throughput, and it is limited by the sample quality. We recently demonstrated that variant-specific PCR can determine SC-2 variant identity in cases of poor sample quality where sequencing fails [41]. Here, we show that variant-specific PCR can be a valuable tool to rapidly identify variant dynamics in WW in a cost-effective manner, which in turn enables a large-scale screening of WW samples to obtain important epidemiological information.…”
Section: Discussionmentioning
confidence: 83%
“…To detect and identify variants of concern, a few studies reported multiple RT-qPCR assays. Most studies identified a partial list of variants such as Alpha and Delta, Delta, or Omicron . Only one study reported a two-reaction multiplex RT-qPCR genotyping assay to differentiate five variants by examining six different mutations simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the WWS studies (66/80, 82.5%) included in this review were conducted in resource-rich countries in Europe and North America (Figure 3). Out of the total of 80 studies, 38 (47.5%) were in Europe [4,9,18,23,28,, 28 (35.0%) in North America (20 studies in the US [11,[84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101], and 8 studies in Canada [102][103][104][105][106][107][108][109]), 10 studies (12.5%) in Asia [110][111][112][113][114][115][116][117], 2 studies in South America [118,119], and 1 study each were conducted in Africa [120] and Australia [121] (Table S1).…”
Section: Geospatial Distributionmentioning
confidence: 99%